Diagnosis and Treatment of Angiography Positive Medium to Large Vessel Childhood Primary Angiitis of Central Nervous System (p-cPACNS): An International Survey - Quan, Angela S.; Brunner, Jürgen; Rose, Benjamin; Smitka, Martin; Hahn, Gabriele; Pain, Clare E.; Häfner, Renate; Speth, Fabian; Gerstl, Lucia; Hedrich, Christian M. (Frontiers in Pediatrics, 2021)
Childhood Primary Angiitis of Central Nervous System (cPACNS) is rare, but can cause significant damage and result in disability or even death. Because of its rarity, the sometimes acute and variable presentation, limited awareness, and the absence of widely accepted diagnostic and therapeutic standards, cPACNS is a diagnostic and therapeutic challenge. Three subcategories of cPACNS exist, including angiography-positive non-progressive p-cPACNS, angiography-positive progressive p-cPACNS which both affects the medium to large vessels, and angiography-negative small vessel sv-cPACNS. Diagnosis and treatment of cPACNS relies on personal experience, expert opinion and case reports/case series. To collect information on diagnostic and therapeutic approaches to transient and progressive PACNS, a survey was shared among international clinicians (German Society for Paediatric Rheumatology, the Paediatric Rheumatology European Society, the German speaking “Network Paediatric Stroke”, and members of the American College of Rheumatology/CARRA Paediatric Rheumatology list server). Results from this survey will be used to define statements towards a consensus process allowing harmonisation of diagnostic and therapeutic approaches and the generation of evidence in a rare condition.